2012
DOI: 10.1160/th11-11-0811
|View full text |Cite
|
Sign up to set email alerts
|

Two global haemostatic assays as additional tools to monitor treatment in cases of haemophilia A

Abstract: Haemophilia A patients with similar levels of factor VIII (FVIII) may have different bleeding phenotypes and responses to treatment with FVIII concentrate. Therefore, a test which determines overall haemostasis may be appropriate for treatment monitoring in some patients. We studied two global haemostatic methods:endogenous thrombin potential (ETP) and overall haemostatic potential(OHP) before and after injection of FVIII concentrate in patients with haemophilia A treated prophylactically and on-demand. A sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 27 publications
3
25
0
Order By: Relevance
“…Eighteen patients treated on demand at the Hemostasis Department and Hemophilia Centre, Belgrade, Serbia, were part of a larger study that included patients treated both on demand and prophylactically [12,13]. On-demand treatment is the replacement of coagulation factors following a bleeding or bleeding-like symptoms.…”
Section: Patientsmentioning
confidence: 99%
See 2 more Smart Citations
“…Eighteen patients treated on demand at the Hemostasis Department and Hemophilia Centre, Belgrade, Serbia, were part of a larger study that included patients treated both on demand and prophylactically [12,13]. On-demand treatment is the replacement of coagulation factors following a bleeding or bleeding-like symptoms.…”
Section: Patientsmentioning
confidence: 99%
“…Absorbance (Abs) at 405 nm is measured each minute for 40 min to construct the fibrin-aggregation curve. The area under the curve is expressed by a summation of the Abs values (Abs-sum) [12]. The latter results have been used in a larger study previously published [12,13].…”
Section: Global Hemostatic Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it is generally accepted that a clinical status depends primarily on FVIII level, it has been shown that measurement of TG can reflect the clinical bleeding phenotype better than the FVIII level [2][3]. Overall Hemostatic Potential (OHP), a method assessing both coagulation and the fibrinolysis may also be a promising tool for the evaluation of hemostatic capacity in hA [3].…”
Section: Dear Sirmentioning
confidence: 99%
“…Overall Hemostatic Potential (OHP), a method assessing both coagulation and the fibrinolysis may also be a promising tool for the evaluation of hemostatic capacity in hA [3].…”
Section: Dear Sirmentioning
confidence: 99%